On the stability of a weighted finite difference scheme for wave equation with nonlocal boundary conditions - Novickij, Jurij; Štikonas, Artūras (Nonlinear Analysis: Modelling and Control, 2014)
We consider the stability of a weighted finite difference scheme for a linear hyperbolic equation with nonlocal integral boundary condition. By studying the spectrum of the transition matrix of the three-layered difference scheme we obtain a sufficient stability condition in a special matrix norm. *The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/2014).